Coronary Vasospasm Secondary to 5-Fluorouracil and Its Management: Case Report - Mustafa Yildirim; Cem Parlak; Cem Sezer; Ramazan Eryilmaz; Cetin Kaya; Mustafa Yildiz (Eurasian Journal of Medicine, 2011)
Although rare, 5-fluorouracil (5-FU) may lead to cardiotoxicity that presents with angina, elevated cardiac enzymes and electrocardiogram (ECG) changes. Coronary vasospasm related to 5-FU is a rare clinical entity in oncological practice and may be seen during both bolus and protracted infusional administration. This toxicity is generally reversible and responds well to conventional anti-angina treatment following discontinuation of infusion. We propose that parenteral diltiazem is an effective and safe approach for the treatment of coronary vasospasm secondary to 5-FU infusion. We present clinical findings and management of a case in which coronary vasospasm occurred during the infusion of the 5-FU component of FOLFIRI-bevacizumab chemotherapy (CT) regimen given for treatment of metastatic rectal cancer.